Impurity‐Induced Robust Trionic Effect in Layered Violet Phosphorus. Issue 1 (19th October 2021) - Li, Yanyong; Cai, Songhua; Lai, Wai Kin; Wang, Chenhao; Rogée, Lukas; Zhuang, Lyuchao; Zhai, Lingling; Lin, Shenghuang; Li, Mingjie; Lau, Shu Ping
Abstract: Trionic effect is a vital excitonic physical phenomenon, which intensively affects the optical and optoelectronic properties of 2D materials. Violet phosphorus (VP) is another allotrope of elemental phosphorus with robust photoluminescence (PL) emission in the visible range. So far, experimental investigations of the excitonic behavior in VP are quite scarce. Herein, the evolution of the PL mechanism in synthesized VP crystals against the Ar + plasma exposure is investigated with emphasis on a conversion from trion to exciton emission. The estimated trion binding energy of VP is ≈109 meV, relatively larger than common layered materials. By analyzing the chemical states and the atomic structures, the conversion mechanism is proposed as follows. The Ar + plasma treatment reduces the stannous SnIP impurities' population, which are incorporated into the VP lattices and serve as the n ‐type dopants leading to the trion formation. Besides, various surface defects (PO x ) can promote the trion‐to‐exciton conversion by withdrawing electrons from VP in the process and act as hole‐trap centers to enhance the photodetection of VP phototransistors. This work reveals that the layered VP crystal can provide an ideal platform to study the excitonic physics and future trionic devices at the 2D limit. Abstract : A novel layered material, violet phosphorus (VP), possesses robust trionic effect with a huge trion binding energy of ≈109 meV. With the trion‐exciton conversion by Ar + plasma exposure, VP's photoluminescence can be modulated based on a combined effect, which is related to the reduction of the population of stannus SnIP impurities and electron withdrawal by the surface defects.